Gender, Age, Hunger, and Body Mass Index as Factors Influencing Portion Size Estimation and Ideal Portion Sizes - Duszka, Kalina; Hechenberger, Markus; Dolak, Irene; Kobiljak, Deni; König, Jürgen (Frontiers in Psychology, 2022)
Portion sizes of meals have been becoming progressively larger which contributes to the onset of obesity. So far, little research has been done on the influence of body weight on portion size preferences. Therefore, we assessed whether Body Mass Index (BMI), as well as other selected factors, contribute to the estimation of food portions weight and the subjective perception of portion sizes. Through online questionnaires, the participants were asked to estimate the weight of pictured foods in the first study. In the second study, the participants indicated how the depicted varying portion sizes of different meals relate to their actual consumed real-life portion sizes. A total of 725 and 436 individuals were included in the statistical analysis in the first and second study respectively. BMI and gender had a small effect on the capacity to estimate the weight of foods. The main predictor for portion size choices was the factor gender with men estimating ideal portion sizes as larger than women. Further, age and hunger together with external and restrictive eating behaviors were among the deciding factors for portion size choices. As expected, externally motivated eaters chose bigger portions while restrictive individual smaller ones. Gender- and age-related differences in portion size preferences likely reflect distinct energy requirements. The individuals with a higher BMI do not differ strongly from other BMI groups in their portion-related preferences. Therefore, other factors such as meal frequency, snacking, or a lifestyle, may contribute more to the onset, development, and maintenance of overweight.